Children using Facebook: teachers' discursive constructions of childhood. Issue 2 (3rd April 2018) - Chang-Kredl, Sandra; Kozak, Stephanie
ABSTRACT: Conceptualizations of childhood are powerful determinants of adults' interactions with children, and technology and social networking systems are affecting the nature of teachers' knowledge of childhood. We analyzed questionnaire responses from 57 elementary-level teachers from Quebec regarding children's use of Facebook . Through discourse analyses, we found four common images of childhood (child as innocent, evil, future adult, and agent) present in the teachers' responses; however, the context of social media brought to fore questions about adult surveillance at a time of generational pliability and teachers' self-understanding in relation to their knowledge of children.